The Therapeutic Effect of Azole and Probiotic Combination on Vulvovaginal Candidiasis: A Literature Review - Ummu Aiman; Sahda Alfreda Putri; Jeniffer Handiokho; Efenina Ginting; Agnes Amalia; Maureen Miracle Stella (Indonesian Journal of Global Health Research, 2025)
One of the most prevalent vaginal infections in the world is vulvovaginal candidiasis. Due to numerous reported cases of antifungal resistance, a combination treatment with synergistic effect is needed. We aimed to examine the effects of combination therapy involving the administration of azoles and probiotics for treating vulvovaginal candidiasis. A comprehensive search of databases (Google  Scholar,  PubMed,  Wiley, Taylor and Francis, ScienceDirect, and SAGE) using ("Candida" OR "candidiasis") AND ("azole") AND ("probiotic" OR "Lactobacillus") AND ("combination therapy" OR "adjunct treatment") as keywords was performed. Titles and abstracts were reviewed for relevance, followed by full-text screening, without any time limitation (until June 20th, 2025). The inclusion criteria was study published in English about women with vulvovaginal candidiasis receiving azole and probiotic combination as medical treatment. A total of 10 included studies were clinical trials [RCT (n=7) and quasi-experimental (n=3)]. All studies were published between 2015 and 2024. The most commonly used azoles are fluconazole (n=5), clotrimazole (n=4), miconazole (n=1), and the dominant probiotics are Lactobacillus rhamnosus (n=5) and Lactobacillus acidophilus (n=6). Included studies used different azole drugs; most studies used fluconazole orally, either a single dose of 500 mg or 50 mg once daily. Each study combined these azole drugs with probiotics containing several strains via either peroral or pervaginal. The combination of azoles and probiotics can enhance the antifungal effects against candidiasis. Probiotics not only enhance the therapeutic efficacy of vulvovaginal candidiasis treatment but also contribute to reducing the risk of azole resistance.